Correction: Genetic differentiation at extreme latitudes in the socially plastic sweat bee Halictus rubicundus. - Bas A Michels; Mariska M Beekman; Jeremy Field; Jodie Gruber; Bart A Pannebakker; Charlotte Savill; Rebecca A Boulton (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0302688.].